Balanced Mechanical and Tribological Performance of High-Frequency-Sintered Al-SiC Achieved via Innovative Milling Route—Experimental and Theoretical Study - Ahmed Fouly; Saud M. Almotairy; Muhammad Omer Aijaz; Hamad F. Alharbi; Hany S. Abdo (Crystals, 2021)
In this study, Al-SiC nanocomposite was fabricated via powder metallurgy route using different innovative high-energy ball-milling techniques (HEBM). The powder mixture was consolidated using high-frequency induction heat sintering process (HFIHS). With the aim of studying the physical, mechanical, and tribological performance of the fabricated nanocomposites. Relative density, hardness, compressive yield strength, Young’s modulus, toughness, elongation, specific wear rate and coefficient of friction were experimentally investigated. A finite element model for the frictional process was built to find out the distribution of contact stresses as result of samples sliding. It was found that the highest the energy of the milling, the more improvement in the mechanical and tribological performance could significantly achieved due to the homogeneous distribution and the excellent bonding effect of the composite. In addition, field emission scanning electron microscope was used for studying the sliding surface morphology in order to explicate the mechanism of the dry wear process.